answersLogoWhite

0


Want this question answered?

Be notified when an answer is posted

Add your answer:

Earn +20 pts
Q: Is 3x cubed 5y cubed 14 simplified?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

3x-8y plus 2x-5-5y simplified?

3x - 8y + 2x - 5 - 5y = 5x -13y - 5


What is -8y-(x-4x) 3y simplified?

If you mean: -8y-(x-4x)+3y then it is 3x-5y simplified


What is the answer to -2x-5y plus 3x-7y?

The given expression can be simplified to: x-12y


What is 13x 2y -10x-7y?

If you mean: 13x+2y-10x-7y then it is an algebraic expression that can be simplified to 3x-5y


What is the equation of the line passing through 3 1 and is parallel to 3x plus 5y equals 6 showing work?

If: 3x+5y = 6 Then: y = -3/5x+6/5 which means it has a slope of -3/5 Parallel equation: y-1 = -3/5(x-3) => 5y-5 = -3(x-3) => 5y = -3x+14 Or as: 3x+5y = 14


What is the answer to 5x plus 10 plus 5y minus 3x plus 1?

5x+10-5y-3x+1=0 <--You start with this. Then move the 10 and 1 to the other side by subtracting them. 5x-5y-3x=-11<--Next combine the x's 2x-3y=-11<--This is the simplified answer.


3x plus 5y equals 48 -3x plus 5y equals 12Solve the system of equations Enter your answer as an ordered pair?

3x+5y=48 5y=48-3x-3x+5y=12 -3x+(48-3x)=12-6x=-36x=65y=48-3(6)5y=30y=6(6,6)


What is 13x plus 2y -10x -7y?

To simplify the expression 13x + 2y - 10x - 7y, you first combine like terms. Group the x terms together and the y terms together: (13x - 10x) + (2y - 7y). This simplifies to 3x - 5y. Therefore, the simplified expression is 3x - 5y.


Which is equivalent to 3x divide by 7 plus 5y divided by 14x?

3x/7 + 5y/14x = 3x*2x/(7*2x) + 5y/14x = (6x2 + 5y)/14x


What is the x-intercept of this equation 3x 5y 9?

The x-intercept is the point where the y-intercept is zero. "3x 5y 9" is not an equation. 3x+5y+9, or 3x-5y+9, are examples of what was meant to be shown.


What is the equation of the line that goes through 3 1 and is parallel to the line 3x plus 5y equals 6?

Known equation: 3x+5y = 6 or y = -3/5x +6/5 Slope of equation: -3/5 Slope of parallel equation: -3/5 Parallel equation: y-1 = -3/5(x-3) => 5y = -3x+14 Parallel equation in its general form: 3x+5y-14 = 0


Simplifying rational expressions 6x-5y plus -3x-4y?

(6x - 5y) + (-3x - 4y) =6x - 5y - 3x - 4y =3x - 9y =3 (x - 3y)